Impact of radiation and heat source/sink on dissipative MHD mixed convection flow of casson nanofluid over a stretching sheet with chemical reaction - Konda, Jayaramireddy; Ganteda, Charankumar; Salleh, Zabidin; Sundaram, Indira; İnç, Mustafa; Ramakrishna, B.; Govindan, Vediyappan (Elsevier, 2025)
This study presents a numerical investigation of transverse magnetohydrodynamic (MHD) Casson nanofluid (CNF) flow over a nonlinear expanding surface, considering the effects of thermal radiation, heat generation/ absorption, and chemical reactions. The research is significant due to its applications in biomedical engineering, polymer manufacturing, and industrial cooling systems, where precise control of heat and mass transfer is essential. The Casson fluid model is adopted to account for non-Newtonian behavior, and the effects of Brownian motion and thermophoresis are incorporated to enhance the understanding of nanoparticle transport mechanisms. The governing boundary-layer equations are converted into ordinary differential equations (ODEs) using similarity transformations. The Homotopy analysis method (HAM) is employed to obtain analytical solutions, providing a deeper insight into the parametric effects on flow characteristics. The study examines the influence of various parameters, including the Casson fluid parameter, Prandtl number (PN) (Pr), magnetic field parameter (M), Brownian motion parameter (Nb), nonlinear stretching parameter (n), Lewis number (Le), thermophoresis parameter (Nt), and chemical reaction rate, on velocity, temperature, and concentration distributions. Unlike previous studies, the PN is treated as a variable parameter to account for temperature-dependent viscosity variations. The findings reveal that increasing the Casson parameter reduces velocity due to enhanced fluid viscosity, while higher magnetic field strength suppresses flow due to Lorentz force effects. Additionally, Brownian motion and thermophoresis significantly impact temperature and nanoparticle concentration profiles, highlighting their importance in nanofluid transport. The study also presents graphical and tabular analyses of skin friction, heat transfer rate, and mass transfer rate, demonstrating their variations with key governing parameters. These results provide valuable insights for optimizing heat and mass transport in complex fluid systems.
Keywords: Casson nanofluid; Magnetic field; Expanding sheet; Radiation; Heat source; Substance response; HAM